2021
DOI: 10.1186/s41938-021-00403-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indigenous the nucleopolyhedrovirus (NPV) of Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) in combination with chlorantraniliprole against Spodoptera species

Abstract: Background The armyworms, Spodoptera exigua (Hübner), and S. litura (Fabricius) (Lepidoptera: Noctuidae) are polyphagous pests of many cash crops. Heavy crop losses have been reported for the fruit and vegetable crops each year owing to the diverse impact on global economies. The present study was aimed to sort out a novel method of pest control using the insect’s own nucleopolyhedrosis virus (NPV) alone and in combination with a new chemistry insecticide chlorantraniliprole. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our results were also in corroboration with the results obtained by other Ali et al (2018) who observed that the mortality of the S. litura larvae increased with dose. The findings of the present study were in line with the findings of Sarwar et al (2021) who carried out an evaluation of NPV against different larval instars. The second instar larvae of Spodoptera species were found to be more susceptible to nucleopolyhedrosis virus in comparison to fourth instar larvae.…”
Section: Dosage-mortality and Time-mortality Response Of S Litura Lar...supporting
confidence: 91%
“…Our results were also in corroboration with the results obtained by other Ali et al (2018) who observed that the mortality of the S. litura larvae increased with dose. The findings of the present study were in line with the findings of Sarwar et al (2021) who carried out an evaluation of NPV against different larval instars. The second instar larvae of Spodoptera species were found to be more susceptible to nucleopolyhedrosis virus in comparison to fourth instar larvae.…”
Section: Dosage-mortality and Time-mortality Response Of S Litura Lar...supporting
confidence: 91%
“…The insecticidal properties of SfMNPV can also vary between the maize strain and rice strain of the fall armyworm [29]. All the above-mentioned limiting factors on the success of baculoviral bioinsecticide led to investigations of enhanced effectiveness through its combination with biorationals or synthetic low-toxicity insecticides on a range of noctuid pests [30][31][32][33]. A dual-action bioinsecticide was also explored using mixed entomopathogens [34][35][36][37], but this was not always conclusive [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Vairimorpha necatrix, formerly known as Nosema necatrix and Thelohania diazoma, is a microsporidium that has been isolated from at least 14 species of field-collected lepidopteran larvae. V. necatrix has been found to infect various species of Lepidoptera, including economically significant agricultural pests such as Pseudaletia unipuncta, Heliothis zea and Heliothis virescens (Sarwar, 2017a). Additionally, it has been observed to infect Autographa californica, Trichoplusia ni, Spodoptera frugiperda, Spodoptera exigua, Spodoptera ornithogalli (Sarwar, 2017b), as well as Plathypena scabra, Pseudoplusia includens and Hyphantria cunea, which have shown potential in controlling the black cutworm Agrotis ipsilon (Sarwar, 2019).…”
Section: Protozoansmentioning
confidence: 99%